Anti‐Corrosive and Zn‐Ion‐Regulating Composite Interlayer Enabling Long‐Life Zn Metal Anodes - Zhou, Shuang; Wang, Yaping; Lu, Haotian; Zhang, Yifang; Fu, Chunyan; Usman, Ibrahim; Liu, Zhexuan; Feng, Mingyang; Fang, Guozhao; Cao, Xinxin; Liang, Shuquan; Pan, Anqiang (Advanced functional materials, 2021)
The Zn metal anode is considered one of the most promising anode choices for aqueous Zn‐based batteries. Nevertheless, dendrites and intricate side reactions have hindered its usage. Herein, an elastic and anti‐corrosive interlayer is introduced to address the problem. The idiosyncratic dielectric behavior of amorphous and nanostructured silicon nitride (Si3N4) is utilized to manipulate the ion kinetics, by uniformly dispersing its particles in polyacrylonitrile (PAN) to fabricate an interlayer attached to Zn metal (PSN‐Zn). PAN serves as an elastic constraint to inhibit drastic dendrite evolution and blocks H2O/O2 corrosion, and Si3N4 with a high dielectric constant can facilitate the ion kinetics and endow uniform Zn deposition. The electrochemical stability and deposition consistency of the Zn anodes are greatly improved, with an extended lifespan of over 800 h at 1 mA cm−2. Even under draconian deep‐discharging (DODZn = 60%) and high current density (10 mA cm−2), the PSN‐Zn anode can still operate stably for over 250 h. The effect of the dielectric property is systematically discussed and verified by experiments and theoretical simulations. Moreover, full cells with vanadium‐ and manganese‐based cathodes also deliver excellent performance, indicating the use of the multifunctional interlayer as an appealing approach for rechargeable aqueous zinc batteries. Side reactions and dendrites can be effectively suppressed by coating an anti‐corrosive and Zn‐ion‐regulating interlayer on the Zn anode. In the layer, polyacrylonitrile acts as an H2O/O2 barrier, and amorphous Si3N4 nanoparticles with special dielectric properties can enhance ion kinetics and endow uniform Zn deposition. The Zn anodes with the coating can deliver good performance even under harsh cycling conditions.